Aptamer-Based Western Blot for Selective Protein Recognition - Wang, Yao; Li, Zhe; Yu, Hanyang (Frontiers in Chemistry, 2020)
Selective protein recognition is critical in molecular biology techniques such as Western blotting and ELISA. Successful detection of the target proteins in these methods relies on the specific interaction of antibody, which often brings high production cost and requires long incubation time. Aptamers represent an alternative class of simple and affordable affinity reagents for protein recognition. And replacing antibodies with aptamers in Western blotting would potentially be more time- and cost-effective. In this work, multiple fluorescent DNA aptamers were isolated by in vitro selection to selectively label commonly used tag proteins including GST, MBP and His-tag. The generated aptamers G1, M1 and H1 specifically bound to their cognate target proteins with nanomolar affinities, respectively. Compared with conventional antibody-based immunoblotting, such aptamer-based procedure gave a cleaner background and was able to selectively label target protein in a complex mixture. Lastly, the identified aptamers were also effective in recognition of different fusion proteins with the same tag, thus greatly expanding the scope of the potential applications of these aptamers. This work provided aptamers as useful molecular tools for selective protein recognition in Western blotting analysis.